FORMULASI STRATEGI UNIT BISNIS LAUNDRY SEPATU (STUDI KASUS DARMAWAN WASH SHOE BOGOR) - Danang Wicaksono; Lukman M. Baga; Tanti Novianti (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Shoes are not only used for daily needs now, but people rather consider that shoes are an important fashion item for their appereance. Despite the growing culture of Indonesian sneakerhead, Darmawan Wash Shoe had recently experiencing decreased sales from 2017 untiI 2019. This research aimed to 1) identifying internal and external factors which are strengths, weaknesses, opportunities and threats that influences the sales of Darmawan Wash Shoe; 2) formulate alternative strategies that can be implemented to increase sales based on the influences of each internal and external factors on Darmawan Wash Shoe; 3) determine the priority from those alternative strategies to be implemented to achieve sales targets in Darmawan Wash Shoe. The methods used in this study are: 1) identification of Darmawan Wash Shoe internal factors using the Internal Factor Evaluation (IFE) method and identification of Darmawan Wash Shoe external factors using the External Factor Evaluation (EFE) method, positioning Darmawan Wash Shoe business using the Internal External (IE) matrix; 2) aIternative strategy formulations using the SWOT matrix method; 4) formulating priority strategies with the Quantitative Stratategy Planning Matrix (QSPM) method. The results of internal and external analysis found that the position of Darmawan Wash Shoe is in quadrant V, the strategy that must be done is market penetration and development product in the QSPM analysis, the main priority strategy is to conduct onIine discount promotions. Keywords: EFE, IFE, QSPM, Startegy Formulation, SWOT